Evaluation of two chlorhexidine – alcohol‐based skin disinfectants in blood donation setting. Issue 4 (29th October 2013) - So, B. K. L.; Chu, C. C. Y.; Ho, P. L.; Chow, K. H.; Leung, J. N. S.; Lee, I. Y. M.; Lin, C. K.; Lee, C. K.
<x xml:space="preserve">Abstract</x> Background Source reduction is important in minimizing bacterial‐contaminated risk of blood products, but previous evaluation of chlorhexidine (CHX) was confounded by inability of Tween and lecithin to neutralize CHX. The study aims to address this limitation and also evaluates the effectiveness of two CHX–alcohol‐based skin disinfectants in blood donation setting. Methods A two‐stage observational study was conducted. A single step 2% chlorhexidine gluconate/70% isopropyl alcohol brush (CHX/IPA‐1) was first compared with current skin disinfection procedure consisting of sequential application of 10% povidone‐iodine and 70% isopropyl alcohol (PI/IPA). Standard plates with conventional neutralizers (0·3% Tween‐80, 0·1% lecithin) were used to enumerate residual bacterial counts. Then, CHX/IPA‐1 was compared with another applicator CHX/IPA‐2 with identical disinfectant contents using in‐house plates with neutralizers (3% Tween‐80, 0·3% lecithin, 0·1% histidine, 0·5% sodium thiosulphate, 3% saponin, 1% ether sulphate) having enhanced ability to neutralize CHX. Results All three products were found to reduce plate counts by > 2 log10 after disinfection. The CHX/IPA‐1 group gave fewer residual bacterial growth on standard plates than PI/IPA group (5·9% vs. 61·7%, P < 0·001). With the use of in‐house plates, residual bacterial growth was of no difference in both CHX/IPA‐1 and CHX/IPA‐2 groups (42·5% vs. 49·4%, P = 0·26). Conclusion Good efficacy was observed with one‐stage application of CHX/IPA in predonation skin disinfection and it could replace PI/IPA. However, the efficacy of CHX/IPA could be grossly overestimated in testing with standard plates because of insufficient neutralization.